INTEGRATING MANGROVE CONSERVATION VALUES INTO PROJECT-BASED LEARNING (PjBL) BIOLOGY TO ENHANCE COLLEGE STUDENT’S ECO-LITERACY - Anju Sansena, Mona; Nur Rachmawati, Rizqi; Rahmayani, Dede (Universitas Cokroaminoto Palopo, 2025)
The global climate crisis identifies mangrove ecosystems as strategic yet vulnerable components prone to degradation, particularly in coastal regions like Tangerang. This study examines the effectiveness of integrating mangrove conservation values into the Project-Based Learning (PjBL) model to improve the eco-literacy of Biology Education students. A quantitative quasi-experimental Pretest-Posttest Control Group Design was applied to 28 students, divided into experimental and control groups. Data were collected through ecological literacy tests, environmental attitude scales (New Ecological Paradigm/NEP), and field skill observations, then analyzed using Independent Sample T-tests and Normalized Gain (N-gain) scores. Results indicate a significant impact (p=0.000) of PjBL integrated with mangrove conservation values across all dimensions of eco-literacy. The experimental group achieved high improvement, with N-gain scores: cognitive (0.74), affective (0.83), and psychomotor (0.76), with the affective aspect being dominant. Direct involvement at sites such as Ketapang Urban Aquaculture effectively fostered ecological responsibility. The study concludes that local conservation-based PjBL transforms students into eco-literate agents of change through direct, hands-on experiences.